Therapeutic Effects of Methanol and Aqueous extract of Terminalia glaucescens (Combretaceae) on Gastro-intestinal Nematodes of Djallonke Sheep - Lem, Mbafor Fidelia; Kingsley, Manchang Tanyi; Paguem, Achille; Payne, Vincent Khan; Tchoumboue, Joseph (European Journal of Applied Sciences, 2026)
Background: Gastrointestinal nematodes (GIN) are a major threat to sheep productivity and endangers animal welfare worldwide particularly in developing countries. They cause loss of production through mortality, weight loss, reduced milk, meat and wool production. Thus, GIN infection is an important limiting factor or constraint in livestock production. Aim: To evaluate the anthelmintic activity of organic and aqueous extracts of stem bark of Terminalia glaucescens against gastrointestinal nematodes of sheep using varieties of in vivo tests. Materials and Methods: Fourty (40) Djallonke sheep acquired natural infection with gastrointestinal nematodes of both sexes, aged 6-10 months old and weighing between 8-15kg, used in bioassay were distributed into 5 groups (n=8). Two experiments using methanol (Groups A to E) and hot water extracts (Groups A’ to E’) were simultaneously carried out. Groups A & A’ received 1.25% dimethyl sulfoxide (DMSO) and distilled water 1ml/10 kg bodyweight (bwt) respectively, Groups B & B’ received Fenbendazole at 6.25mg/kg bwt, Groups C & C’, D & D’ and E & E’ received doses of 125, 250 and 500 mg/kg bwt of each extract. Sheep were subjected to different treatment with single dose of synthetic drug and double doses of plant extracts. Results: Methanol extract for all the doses tested was active in vivo on the adults of GIN, and reduced significantly (p<0.05) the faecal egg count (FEC) and total warm count (TWC) of the nematodes. The dose rate 500mg/kg showed the highest nematocidal activity of 77, 6% FEC and 73, 5% TWC reduction 14 days post-treatment. For hot water extract, these numbers were 65,3% and 62,1% for FEC and TWC respectively at the same dose for the same period of treatment. Conclusion: These results suggest the possible use of this medicinal plant in the control of gastrointestinal nematodes in sheep and justify their use in traditional veterinary practices.